Menakar Penerapan Konsep Dinar Dirham di Indonesia - Candrakusuma, Mushlih; Kurniasari, Evita (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2023)
Money is one of the pillars of the economy. Money facilitates the process of exchanging commodities and services. Every process of production and distribution must use money. Money has the main function as a medium of exchange, and is passed on to other functions such as standard of value, store of value, unit of account. Based on a political-ideological perspective, returning the concept of dinar dirham money in the context of Islam and Indonesianness is something that is urgent (daruri), in order to achieve economic prosperity for the people and the nation. The concept of the dinar dirham can be an alternative solution to solving economic problems in society. Meanwhile, based on a juridical-normative perspective, the application of the dinar dirham in the Indonesian context is experiencing real problems. The application of the dinar and dirham system is irrelevant because the rupiah is the only valid means of payment in national economic activities.